Service learning experiences of doctor of physical therapy students with a severe mental illness population - Sean Karyczak; Ann A Murphy; Michelle Zechner; Ellen Z Anderson; Anthony Zazzarino (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Physical therapists provide important services to improve physical health for the general population; however, physical therapy interventions are less utilized with underserved populations such as those with severe mental illness (SMI). The quality of services for these populations is impacted in part by negative provider attitudes and lack of preparation to work with the SMI population. This study examined the impact of structured educational field experience on the physical therapist's attitudes and knowledge about working with the SMI population. This will inform future educational practices to best prepare students to provide quality of healthcare to the population. MATERIALS AND METHODS: Seven graduates of a doctor of physical therapy (DPT) program from a Mid-Atlantic University in the United States who participated in an SMI service-learning (SL) experience completed a semi-structured qualitative interview in 2016. Questions about how the experience impacted their current work were asked. Interviews were digitally recorded, transcribed, and examined using interpretive phenomenological analysis. Coding and investigator triangulation were conducted. All interviews reached thematic saturation. RESULTS: The graduated DPT students reported attitudinal changes toward people with SMI through qualitative interviews. They reported an improvement in their skills, greater competence to work with the SMI population, and an increased focus in the use of person-centered services. CONCLUSIONS: The results of this study suggest that DPT students gain an understanding of both the SMI population and themselves during SL. Using SL as part of the DPT educational curriculum can offer students and the opportunity to build confidence in working with the SMI population. SL can also improve their skills and attitudes toward the population, key areas that are identified as barriers to receiving quality physical healthcare among the SMI population.